Development and validation of the Exercise Dependence and Elite Athletes Scale - McNamara, J.; McCabe, M. P. (Performance Enhancement & Health, 2013)
Aims Exercise Dependence (EXD) is a clinical condition associated with physical and psychological risks for elite athletes. This paper describes the development and preliminary validation of the Exercise Dependence (EXD) and Elite Athletes Scale (EDEAS). Method Study 1 generated 27 preliminary items for the EDEAS based on the perceptions of coaches of elite athletes (n = 86). In Study 2, the initial EDEAS was administered to 234 elite athletes and the responses were factor analyzed. Results Six factors emerged: Unhealthy Eating Behavior, Conflict and Dissatisfaction, More Training, Withdrawal, Emotional Difficulties, Continuance Behavior. Item-total correlations for individual subscales and internal reliabilities were acceptable (i.e., a > .60). The final 24-item EDEAS was validated against an alternative measure of EXD, and was shown to be highly correlated. Conclusion The EDEAS shows acceptable preliminary psychometric properties as a measure of EXD among elite athletes.